Oman : Report on Observance of Standards and Codes (ROSC)-Data Module Volume I. (IMF Staff Country Reports; Country Report, 2015)
This paper discusses the findings and recommendations of the Report on Observance of Standards and Codes (ROSC)-Data Module for Oman. It is observed that Oman has made significant progress in the compilation and dissemination of macroeconomic statistics since the 2004 ROSC mission. The main progress has been achieved in monetary statistics, price indices, and balance of payments, in particular the introduction of the producer price index, and improvements in data relevance, transparency, classification, and sectorization. The report also recognizes the need for Oman to move to higher data standards and identifies shortcomings in statistical practices and products that remain to be addressed.